Arcobacter butzleri strains isolated from different sources display adhesive capacity to epithelial cells in vitro - Fernandéz, Heriberto; Flores, Sandra; Inzunza, Fernanda (Acta Scientiae Veterinariae, 2018)
Background : : : : The genus Arcobacter, belonging to the family Campylobacteraceae, includes polar flagellated, curved or spiral rod shaped bacteria firstly described as Vibrio/Spirillum organisms and later as aerotolerant Campylobacterlike microorganisms. Currently, this genus comprises nine validated species and a candidatus. Among Arcobacter species, Arcobacter butzleri is recognized as a zoonotic agent and the most common species of the genus isolated from environmental water, food and clinical samples. Recently, this species was considered a serious hazard to human health. However, their pathological properties, potential virulence factors as well as their clinical significance remain uncertain or not completely defined. The aim of this study was to establish the ability of 78 A. butzleri strains isolated from different sources to adhere to HEp-2 cells in vitro. Materials, Methods & Results: All the strains were isolated using first an enrichment medium incubated aerobically at 26 ºc for 48 h. after that, 100 ?l of the broth were streaked onto Arcobacter selective agar plates and incubated at 26 °c for 72 h. all the strains were identified phenotypically using standard assays. Definitive identification was achieved using a multiplex polymerase chain reaction. Adhesive capacity was determined infecting hep-2 cells with the strains under study following scaletsky’s et al. protocol, with slight modifications. An adherent Escherichia coli isolated was included as a positive control, whereas uninoculated cell lines were used as negative controls. Adhesion results were expressed as the percentage of hep-2 cells showing adhering bacteria and the number of bacteria (± sd) adhered to cells was determined. Strains were considered as adherent, if at least 20% of hep-2 cells showed one ore more adhered bacteria. Adherence was also demonstrated by scanning electronic microscopy. All the strains showed adhesive capacity to HEp-2 cells in vitro. The lowest adhesion percentage (27%) was observed in a strain isolated from dog feces. In at least one strain per source it was possible to observe 100% adhesion. The lowest number of adhered bacteria (1.03 ± 1.53) was observed in a strain isolated from river water and the highest number (76.6 ± 5.59), in a strain isolated from duck feces. Discussion: Regardless of their isolation source, the 78 Arcobacter butzleri strains tested in the present study were able to adhere to HEp-2 cells in vitro. This property was demonstrated in different proportions by other authors in strains isolated from environmental, meat and human fecal samples. Electronic scanning microscopy shows curved bacilli adhering to HEp-2 cells forming a microcolony-like arrangement. This may occur in a stepwise mechanism. First, A. butzleri adhere to HEp-2 cells and then, due to their capacity to form biofilms, interbacterial adherence can be expressed. The capacity of A. butzleri to form biofilms attaching to stainless steel, copper and glass has been demonstrated in previous studies. Further studies are necessary to elucidate the molecular and cellular mechanisms accounting for this biological property; and hence, its actual role in the colonization of human and animal intestinal epithelium by A. butzleri.